High-quality neurosurgeon communication and visualization during telemedicine encounters improves patient satisfaction. (December 2021) - Rodrigues, Adrian; Li, Guan; Zhang, Michael; Jin, Michael C.; Hayden-Gephart, Melanie
Highlights: High quality communication is one of the key predictors of patient satisfaction. Patients who perceived physician difficulty in seeing them reported far lower scores. Patients with difficulty understanding the provider reported perfect scores less often. Abstract: Introduction: While recent studies have focused on confirming satisfaction with telemedicine during the coronavirus disease 2019 (COVID-19) era, we leveraged a novel survey instrument to identify associations between patient experience and telemedicine-specific factors such as device selection, audio/visual resolution, and connection stability. Methods: Telemedicine visit data were gathered from our institution between June 22, 2020 and February 14, 2021. Each patient indicated their overall visit score, likelihood-to-recommend (LTR) score, and device used for the encounter. Remaining questions were randomly distributed to patients to ensure equal distribution across respondents. Results: Over 34 weeks, there were 901 unique neurosurgical telemedicine visits linked to a post-visit survey at our institution. The LTR top box score percentage showed no significant change across 34 weeks (p = 0.218). After adjusting across available covariates, patients who experienced wait times exceeding 20 min were significantly less likely to report high overall scores (aOR: 0.12; 95% CI: 0.03–0.41; p = 0.001). Patients who indicated they were less able to understand the provider (aOR: 0.22; 95% CI: 0.07–0.66; p = 0.007), or who indicated the provider was not able to properly see them (aOR: 0.11; 95% CI: 0.03–0.43; p = 0.002) were associated with substantially lower overall scores. Visits with interrupted connectivity or those forced to move to a regular phone call were not important predictors of overall score. Conclusions: In the largest description of patient satisfaction with telemedicine in the neurosurgical setting during the COVID-19 era, we identified timely and high-quality physician-patient visualization and communication as among the most important predictors of patient satisfaction in virtual settings.